’I Generally ... Participate for a Change’. An analysis of everyday political practices - Gambardella, Maria Grazia; Magaraggia, Sveva (PARTECIPAZIONE E CONFLITTO, 2026)
In a context of growing inequalities and institutional disaffection, young women in Italy are redefining political subjectivity through everyday practices of care, solidarity, and commoning. Drawing on a qualitative study conducted from 2019 to 2022 within the PRIN project “Mapping Youth Futures: Forms of Anticipation and Youth Agency”, this contribution explores the experiences of 20 women aged 25–34 from Milan, Naples, Cosenza, and Cagliari. Through an intersectional lens, it highlights how they build new political subjectivities in extra-institutional spaces, centres of daily life and meaning-making. Participants transform the margins into feminist commons, into spaces of political experimentation. Their prefigurative practices contest the neoliberal enclosures of care and time, revealing a shift from institutional allegiances to life-making as a form of politics. The article contributes to debates on youth participation by showing how gendered and generational inequalities can act as catalysts for insurgent agency.